Oral Health in Africa: Building Research and Policy Capacity for Sustainable Change (Nigerian Dental Journal, 2026)
Oral health disparities in Africa are stark, characterized by limited access, fragmented data systems, low political will, and persistent underfunding. With the WHO Global Oral Health Action Plan 2022–2030 calling for integration, prevention, and equity, African researchers and institutions are stepping into leadership roles to drive contextualized, data-informed, and sustainable solutions. This perspective synthesizes insights from African-led initiatives, including collaborative research networks, institution-based innovations, and field trial systems, which are designed to generate locally relevant evidence for clinical interventions and future research. This article draws on experiences across subregions and institutions, informed by the "Oral Health in Africa" symposium at the 2025 International Association for Dental Research (IADR) General Session. The article covers community field trials in Egypt, the initiative of the Intercountry Centre for Oral Health in Nigeria, and continent-wide research networks. It highlights opportunities for transformative change in African oral health and outlines priorities for data generation, policy alignment, institutional coordination, and funding strategies necessary to deliver on the global oral health agenda. Key words: Oral Health Policy, Research Capacity-Building, Health Systems Strengthening, Africa, Universal Health Coverage (UHC), Community-Based Interventions, WHO Global Strategy.
Keywords: Oral Health Policy, Research Capacity-Building, Health Systems Strengthening, Africa, Universal Health Coverage (UHC), Community-Based Interventions, WHO Global Strategy.